Moving away from library-centrism: 7 ideas for using YouTube in the library - Leiva-Aguilera, Javier (Anuario ThinkEPI, 2015)
YouTube is the world´s third most popular internet search engine, and second in search volume, in addition to being the fastest-growing video format and the one that big social web platforms are betting on. Internet users solve many of their needs by learning from the content of videos posted by other users or organizations in that format. In this context, libraries have both an opportunity and the obligation to respond. Increasingly, many librarians are venturing into the world of video, but in most cases they do it from a bibliocentric perspective rather than a focus on the user´s needs or end goals. The text shows examples of uses and offers some suggestions for improvement.